2022
DOI: 10.3389/fvets.2022.861233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Temporal Changes in Microbial Communities in Hyalomma dromedarii Collected From Camels in the UAE Using High-Throughput Sequencing

Abstract: Ticks (Acari) are ectoparasites of animals that harbor communities of microbes of importance to animal and human health. Microbial communities associated with ticks exhibit temporal patterns of variation in their composition, with different genera dominating at different times of the year. In this study, molecular tools were used to assess the composition of the microbial communities associated with Hyalomma dromdarii. Adult ticks were collected every month for 1 year from 25 camels in the UAE. A total of 12 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In previous studies Hyalomma dromedarii was the most common tick species found on camels, accounting for 90% of infestations 17,[22][23][24][25][26][27] . However, we observed a considerable abundance of H. rufipes on camels.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies Hyalomma dromedarii was the most common tick species found on camels, accounting for 90% of infestations 17,[22][23][24][25][26][27] . However, we observed a considerable abundance of H. rufipes on camels.…”
Section: Discussionmentioning
confidence: 89%
“…Hyalomma dromedarii has been found with a high prevalence in camels in various studies [25,36]; therefore, the knowledge about the diversity of viruses in these ticks is crucial for surveillance strategies and for the management of any future tick-borne viral disease outbreak in the country. It should be mentioned that despite the fact that H. dromedarii is the most prevalent tick species on camels in the UAE, its microbiome is still poorly explored, despite the publication of few studies [37,38] that characterized the bacterial communities associated with it. Therefore, the current work sheds light on unexplored viral communities, In this study, for molecular identification of tick species, we used the 16S rRNA sequences of H. dromedarii from UAE that showed 99.75% similarity with H. dromedarii identified from Pakistan (OL307008), 99.50% similarity with sequences of H. dromedarii from India (LC661680), UAE (MZ976772) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in tick viromes between our study and Zakham et al [40] could simply be due to a temporal mismatch since their samples were collected later in the year (between July and October) while ours was collected during June. Evidence from camel tick microbiomes indicates that microbial communities in ticks differ substantially during the course of a year, with notable increases in certain microbes at specific times in the year [38]. Since ecological conditions influence viruses as well, it is expected that certain groups or genera of viruses will dominate at certain times of the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. pseudotuberculosis infections have been reported in several other species, both domestic and wildlife [14][15][16][17][18]. Nevertheless, C. pseudotuberculosis in suids has rarely been described, (e.g., an infection of pigs from two different farms in Spain) [19], as most infections in wild boars and pigs are caused by C. ulcerans [4,20,21], sometimes recently classified as novel C. sylvaticum [22][23][24].…”
Section: Introductionmentioning
confidence: 99%